A Case Study on Non Performing Loans: Hong Leong Finance's Experience - Chew, Shek Nee (1999)
HLFB is one of the leading financial institutions in the country. The company has achieved quantum leap in the increase of the number of branches at the end of 1993 with the acquisition of Visia Finance Berhad. The company was the first finance company in the country to computerize the deposit and loans business between 1981 and 1985. In 1999, HLFB has embarked on opening "In Store" branches. The loan base of the company had increased rapidly, especially from year 1996 to 1997, from RM5,721 million to RM7,544 million and the loan base had grown by 32 percent within the stipulated period. Due to the high loan base, the company has embarked on loan regionalization (decentralization) in September 1996. With the regionalization, it reduces bottleneck in head office. Non-performing loans (NPLs) of the company is rising, from RM177 million in December 1995 to RM1,166 million in March 1999. In terms of percentage, the rate had increased from 4.4 percent to 16.6 percent within the stipulated period. The Chief Operating Officer was very concerned on the rising NPLs and the manager of credit control department was requested to look into the issue. In the past, the company had focussed its lending on corporate loans. The case reveals that corporate loans had contributed to majority of the NPLs and Kuala Lumpur Main office and Johore Bahru Regional loan centre were the two offices that had the highest NPLs rate. To overcome the problem faced by HLFB, two approached were recommended to implement for the reduction of NPLs rate. These two approaches are an immediate approach and preventive approach. Eight different ways to reduce the NPLs under immediate approach were recommended. A preventive approach is quality lending. This approach is used to prevent new loans from becoming problem loans. In this approach, more emphasize is based on quality instead of quantity. Recommendation was make to change the portfolio mix of the company, that is to go for more consumers lending instead of corporate lending, as the risk for corporate loans is higher. To ensure a successful implementation and also to achieve a desirable result, HLFB must always improve the process by going through the process of Planning, Deploying and Reviewing.